Search for a light charged Higgs boson in t →H +-b decays, with H+- →cs, in pp collisions at √s = 13 TeV with the Atlas detector - Aad, Georges; Ackermann, Anke; Baltes, Lisa Marie; Bartels, Falk; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; Sanfilippo, Lorenzo; Schultz-Coulon, Hans-Christian; et al. (The European physical journal. C, Particles and fields, 2025)
A search for a light charged Higgs boson produced in decays of the top quark, → H^{± } b$$with $$H^{± } → cs$$, is presented. This search targets the production of top-quark pairs $$t\bar{t} → Wb H^{± } b$$, with → \ell ν $$($$\ell = e, μ $$), resulting in a lepton-plus-jets final state characterised by an isolated electron or muon and at least four jets. The search exploits b-quark and c-quark identification techniques as well as multivariate methods to suppress the dominant $$t\bar{t}$$background. The data analysed correspond to $$140\hbox { fb}^{-1}$$of $$pp$$collisions at $$\sqrt{s} = 13\hbox { TeV}$$recorded with the ATLAS detector at the LHC between 2015 and 2018. Observed (expected) 95% confidence-level upper limits on the branching fraction $$\mathscr {B}(t→ H^{± } b)$$, assuming $$\mathscr {B}(t→ Wb) + \mathscr {B}(t → H^{± } (→ cs)b)=1.0$$, are set between 0.066% (0.077%) and 3.6% (2.3%) for a charged Higgs boson with a mass between 60 and 168 GeV.
Im Titel steht jeweils +- untereinander und ist hochgestellt
Gesehen am 13.11.2025
ATLAS Collaboration: G. Aad, A. Ackermann, L.M. Baltes, F. Bartels, M. Dunford, S. Franchino, Junkermann, T., Mkrtchyan, T., P.S. Ott, Rasslof, D. F., L. Sanfilippo, H.-C. Schultz-Coulon, V. Sothilingan, R. Stamen, P. Starovoitov, S.M. Weber, M. Wessels und viele weitere